2014
DOI: 10.3174/ajnr.a4138
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Correlates of Cognitive Impairment in Essential Tremor

Abstract: BACKGROUND AND PURPOSE: Impairment of cognitive functions occurs in essential tremor, though the mechanism is largely unknown. The aim of this study was to find microstructural correlates of cognitive dysfunction seen in essential tremor by using DTI and neuropsychological assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Since PWT has overlapping features with ET and WC, it becomes important to evaluate the neuropsychological profile in these patients to get a better insight into the pathogenesis of the disorder. In our study, there was decreased FA value in structures such as ATR, IFO, and ILF which had significant correlation with testrelated executive domain in patients with ET as highlighted by Bhalsing et al [35]. In addition, many areas found to be significantly involved in our study have been implicated to have a role in psychiatric disorders such as bilateral posterior cingulate gyrus and precuneus in early Alzheimer's disease (AD) [37].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Since PWT has overlapping features with ET and WC, it becomes important to evaluate the neuropsychological profile in these patients to get a better insight into the pathogenesis of the disorder. In our study, there was decreased FA value in structures such as ATR, IFO, and ILF which had significant correlation with testrelated executive domain in patients with ET as highlighted by Bhalsing et al [35]. In addition, many areas found to be significantly involved in our study have been implicated to have a role in psychiatric disorders such as bilateral posterior cingulate gyrus and precuneus in early Alzheimer's disease (AD) [37].…”
Section: Discussionsupporting
confidence: 52%
“…Bhalsing et al [34] in their study on ET have found significant gray matter atrophy correlating with impaired cognitive domains. In another study, Bhalsing et al [35] reported a significant correlation between scores of neuropsychological test and DTI parameters in ET.…”
Section: Discussionmentioning
confidence: 96%
“…The areas outside CTC were linked to nonmotor ET symptoms (Benito‐León et al., 2017; Bhalsing et al., 2014, 2015), which provides further evidence for the pathophysiological complexity of ET.…”
Section: Introductionmentioning
confidence: 67%
“…WM microstructure in abovementioned bundles was related to various neuropsychological outcomes in ET (Bhalsing et al., 2015), while our study linked WM blobs within these tracts to objective tremor measurements reflecting abnormal motor functions. These relationships were in partial agreement with an association between FTM scale and fronto‐parietal WM deficits demonstrated previously (Klein et al., 2011).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation